Behavioral addictions. (February 2015) - Robbins, TW; Clark, L
Highlights: What the new DSM-5 means for the concept of behavioral addiction. Common theoretical framework for substance addiction, behavioral addictions and OCD. Pathological gambling as a prototypical behavioral addiction. Impulsivity and compulsivity in behavioral addictions. Abstract : Behavioral addictions are slowly becoming recognized as a valid category of psychiatric disorder as shown by the recent allocation of pathological gambling to this category in DSM-5. However, several other types of psychiatric disorder proposed to be examples of behavioral addictions have yet to be accorded this formal acknowledgment and are dispersed across other sections of the DSM-5. This brief review marks this important point in the evolution of this concept and looks to future investigation of behavioral addictions with the theoretical frameworks currently being used successfully to investigate substance addiction and obsessive-compulsive disorder, in a potentially new spectrum of impulsive-compulsive disorders.